Vinasse concentration by microfiltration followed by nanofiltration with membrane - Gomes, Maria Thereza de Moraes Santos; Eça, Kaliana Sitonio; Viotto, Luiz Antonio (Pesquisa Agropecuaria Brasileira, 2011)
The objective of this work was to evaluate vinasse concentration by microfiltration (MF) followed by nanofiltration (NF). The experiments were carried out in the laboratory, at 60°C and 500 rpm, using vinasse with 2.8% total solids (TS) in order to assess the influence of pressure on permeate flux and TS retention. Pressure ranged from 1.0 to 3.4 bar for MF, and from 15 to 35 for NF. A membrane cellulose with molecular weight cutoff of 100 kDA was used for MF, and a polyethersulfone (PES) membrane of 300, 500, and 1,000 Da was used for NF. MF at 1.8 bar was selected, because of its good flux and lower energy consumption, and the permeate obtained was subjected to NF. NF showed TS retention of 47–75%, and the highest permeate flux was obtained with PES 1,000 Da at 35 bar. The final concentrate has 4% of TS and is considered appropriate for soil use, in terms of chemical oxygen demand and TS content.
Keywords: permeate flux; cellulose membrane; polyethersulfone membrane; total solids retention